Evaluation of the ITZ modification efficiency via aggregate surface coating with nano SiO2 (NS) and its influence on properties. (December 2022) - Lyu, Kai; Sun, Baoyin; Liu, Xiaoyan; Xie, Xian; Liu, Ruidan
Abstract: In order to effectively refine the porous microstructure of interfacial transition zone (ITZ) region in cement-based materials, the nano SiO2 (NS) was introduced into the mixture via aggregate pre-immerging in NS suspension to directly regulate the formation of ITZ microstructure. For comparison, a corresponding content of NS was directly added to the mixture during the casting process. The macro mechanical properties and micro pore structures of the specimens with varying modification methods and NS contents were assessed. The ITZ microstructures (in terms of porosity distribution and nano mechanical properties) were quantitatively characterized via the combination of BSE-SEM and nano indentation techniques. The results demonstrate that both modification methods could refine the microstructure of the bulk paste and ITZ. The directing adding method can more effectively modify the microstructure of the bulk paste with certain NS dosage (no more than 3%). At higher dosage, due to the agglomeration of the NS, the difference between two methods was not obvious. For ITZ modification, the aggregate pre-immerging method has more profound effect, from the aspects of reducing the ITZ thickness and decreasing the porosity of region in the extreme vicinity of aggregate surface (0–10 µm).